Context of situation in the old linguistic lesson "significance and origin" - Awad, Sami; Mannoun, Yasser (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Meaning precision and fulfillment has been the sole aim of any researcher in language, and since meaning is the outcome of grammatical structure in one specific context, that researcher must not prefer one to the other In other words, all of the grammatical aspects fall in the trap of one controversial relation when it comes to meaning interpretation Therefore, I have tackled the concept of ' situation context ' in my research and the related terminologies and its impact in the field of language , the impact of the religious factor in attracting the old scientists to the significance of grammatical from and context, the outcome of both and to what extent those scientists have relied upon them when interpreting Qur'anic text, lines of poetry only to figure out of them some new rules.